Metaphysics of numbers in philosophy of Pythagoras (Journal of Philosophy Culture and Political Science, 2020)
Pythagoras and his followers wrote works related to abstract numbers in Greek philosophy and theytried to create a philosophy of infinite being on the basis of mathematics. They believed that numberswere created by God and characterized numbers as religious phenomenon and thought that the wholeworld consists of these numbers and their scope. Pythagoras was the author of the word: “Ruler of theworld is numbers. Numbers rule the world”. In the views of Pythagoras, “without numbers, nothing canbe understood or learned. Therefore, numbers carry the root of all developments, and there is nothingwiser than that. That means, these numbers tend to be God. In ancient civilizations, Judaism, Christianityand Islamic philosophy – the philosophy of this Pythagoras was based on an interest in the ontologicalcharacteristics of numbers. Positive integers, called natural numbers, are one of the most amazingdiscoveries of the human brain. The history of mankind amazes with the mystical significance of thenumbers of Pythagoras even today, which has not lost its relevance. This article discusses the relation ofnumbers from 1 to 10 (including 10) and its ontological and metaphysical structure that has been studiedsince the time of Pythagoras with the infinite being.Key words: concept of numbers, Pythagoras, metaphysics of numbers, symbol, infinite being.